2020
DOI: 10.3390/genes11121414
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Sequencing Studies and Gene Expression Profiling in Familial Meniere Disease

Abstract: Familial Meniere Disease (FMD) is a rare inner ear disorder characterized by episodic vertigo associated with sensorineural hearing loss, tinnitus and/or aural fullness. We conducted a systematic review to find sequencing studies segregating rare variants in FMD to obtain evidence to support candidate genes for MD. After evaluating the quality of the retrieved records, eight studies were selected to carry out a quantitative synthesis. These articles described 20 single nucleotide variants (SNVs) in 11 genes (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…A recent study found that non-coding variants in CRKL were significantly associated with risk for conotruncal heart defects in individuals with 22q11.2DS (12). Many genes have been related to hereditary non-syndromic hearing loss and Ménière's disease (13)(14)(15)(16). It is therefore possible that rare variants in these genes could modify audiovestibular phenotype by interacting with TBX1 in 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that non-coding variants in CRKL were significantly associated with risk for conotruncal heart defects in individuals with 22q11.2DS (12). Many genes have been related to hereditary non-syndromic hearing loss and Ménière's disease (13)(14)(15)(16). It is therefore possible that rare variants in these genes could modify audiovestibular phenotype by interacting with TBX1 in 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…Familial aggregation in MD has been described in 9-10% of European descendant population, showing an autosomal dominant inheritance pattern in most families. 1 Despite familial MD displays extensive genetic heterogeneity, 2 we recently observed multiple families carrying rare variants in genes encoding proteins involved in the structure of the hair cells stereocilia and their attachment to the tectorial membrane (TM): an enrichment of rare missense variants in the OTOG gene was found in 15 unrelated MD families 3 and other 9 families showed rare heterozygous variants in the MYO7A gene. 4 In this study, we have performed bioinformatic analyses in exome sequencing data obtained from patients of 77 families with MD to better understand the genetic underpinnings of the disease.…”
Section: Dear Editormentioning
confidence: 99%
“…Pablo Roman-Naranjo 1,2,3,4 Alberto M. Parra-Perez 1,3,4 Alba Escalera-Balsera 1,2,3 Andres Soto-Varela 5,6 Alvaro Gallego-Martinez 1,2,3 Ismael Aran 7 Nicolas Perez-Fernandez 8 David Bächinger 9 Andreas H. Eckhard 9 Rocio Gonzalez-Aguado 10 Lidia Frejo 1,2,3 Jose A. Lopez-Escamez 1,2,3,4…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 99%
“…Familial aggregation in MD has been described in 9-10% of European descendant population 19 . Most families show an autosomal dominant inheritance pattern and rare missense variants in several genes have been described in unrelated MD families 20,21 . Nevertheless, none of these variants has been reported in other MD families, supporting genetic heterogeneity in familial MD.…”
Section: Introductionmentioning
confidence: 99%